Non-invasive detection of liver fibrosis: MR imaging features vs. MR elastography - Venkatesh, Sudhakar K. (Abdom Imaging, 2015)
PURPOSE: To compare accuracy of morphological features of liver on MRI and liver stiffness with MR elastography (MRE) for detection of significant liver fibrosis and cirrhosis. MATERIALS AND METHODS: In this retrospective study, we evaluated 62 patients who underwent liver MRI with MRE and histological confirmation of liver fibrosis within 6 months. Two radiologists, blinded to histology results, independently evaluated liver parenchyma texture, surface nodularity, signs of volumetric changes and portal hypertension for presence of significant fibrosis and cirrhosis. Two more readers independently calculated mean liver stiffness values with MRE. Interobserver agreement was evaluated with kappa and intra-class correlation coefficient (ICC) analysis. Diagnostic accuracy was assessed with area under receiver operating characteristic (AUROC) analysis. Comparison of AUROCs of MRI and MRE was performed. RESULTS: Liver fibrosis was present in 37 patients. The interobserver agreement was poor to good (kappa= 0.12 - 0.74) for MRI features and excellent for MRE (ICC, 0.97, 95% CI, 0.95-0.98). MRI features had 48.5-87.9%sensitivity, 55.2%-100%specificity and 71.5-81.6% accuracy //for detection of significant fibrosis. MRE performed better with 100% sensitivity, 96.5% specificity and 98.9% accuracy .For the detection of cirrhosis, MRE performed better than MRI features with 88.2% sensitivity (vs.41.2-82.3%), 91.1% specificity (vs. 64.4-95.6%) and 93.5% accuracy (vs. 60.6%-80.5%) Among the MRI features, surface nodularity and overall impression had the best accuracies of 80.3% and 81.6% for detection of significant fibrosis respectively. For cirrhosis, parenchyma texture and overall impression had the best accuracies of 80.5% and 79.7% respectively . Overall, MRE had significantly greater AUROC than MRI features for detection of both significant fibrosis (0.98.9 vs 0.71-0.82, p<0.001) and cirrhosis (0.93.5-vs. 0.61 -0.80.5, p<0.01). CONCLUSION: MRE is superior to MRI for the non-invasive diagnosis of significant liver fibrosis and cirrhosis.